Chart of breaking up for three-dimensional task to heat conductivity - Bukenov, M.M.; Bakaуeva, G.B. (Bulletin of the Karaganda University. Mathematics Series, 2015)
Investigated the splitting scheme for three - dimensional heat equation reducible to the three - point progacam. Conducting numerical implementation of the scheme and the practical applicability. Numerical realisasi scheme stabilizing moravci and its comparison with the splitting scheme showed the practical effectiveness of the proposed algorithm. The results of the calculations are shown in the table and give analysis.